Autophagy inhibition prevents glucocorticoid-increased adiposity via suppressing BAT whitening. Issue 3 (3rd March 2020) - Deng, Jiali; Guo, Yajie; Yuan, Feixiang; Chen, Shanghai; Yin, Hanrui; Jiang, Xiaoxue; Jiao, Fuxin; Wang, Fenfen; Ji, Hongbin; Hu, Guohong; Ying, Hao; Chen, Yan; et al.
ABSTRACT: The mechanisms underlying glucocorticoid (GC)-increased adiposity are poorly understood. Brown adipose tissue (BAT) acquires white adipose tissue (WAT) cell features defined as BAT whitening under certain circumstances. The aim of our current study was to investigate the possibility and mechanisms of GC-induced BAT whitening. Here, we showed that one-week dexamethasone (Dex) treatment induced BAT whitening, characterized by lipid droplet accumulation, in vitro and in vivo. Furthermore, autophagy and ATG7 (autophagy related 7) expression was induced in BAT by Dex, and treatment with the autophagy inhibitor chloroquine or adenovirus-mediated ATG7 knockdown prevented Dex-induced BAT whitening and fat mass gain. Moreover, Dex-increased ATG7 expression and autophagy was mediated by enhanced expression of BTG1 (B cell translocation gene 1, anti-proliferative) that stimulated activity of CREB1 (cAMP response element binding protein 1). The importance of BTG1 in this regulation was further demonstrated by the observed BAT whitening in adipocyte-specific BTG1-overexpressing mice and the attenuated Dex-induced BAT whitening and fat mass gain in mice with BTG1 knockdown in BAT. Taken together, we showed that Dex induces a significant whitening of BAT via BTG1- and ATG7-dependent autophagy, which might contribute to Dex-increased adiposity. These results provide new insights into the mechanisms underlying GC-increased adiposity and possible strategy for preventing GC-induced side effects via the combined use of an autophagy inhibitor. Abbreviations: ACADL: acyl-Coenzyme A dehydrogenase, long-chain; ACADM: acyl-Coenzyme A dehydrogenase, medium-chain; ACADS: acyl-Coenzyme A dehydrogenase, short-chain; ADIPOQ: adiponectin; AGT: angiotensinogen; Atg: autophagy-related; BAT: brown adipose tissue; BTG1: B cell translocation gene 1, anti-proliferative; CEBPA: CCAAT/enhancer binding protein (C/EBP), alpha; CIDEA: cell death-inducing DNA fragmentation factor, alpha subunit-like effector A; CPT1B: carnitine palmitoyltransferase 1b, muscle; CPT2: carnitine palmitoyltransferase 2; CQ: chloroquine; Dex: dexamethasone; eWAT: epididymal white adipose tissue; FABP4: fatty acid binding protein 4, adipocyte; FFAs: free fatty acids; GCs: glucocorticoids; NRIP1: nuclear receptor interacting protein 1; OCR: oxygen consumption rate; PBS: phosphate-buffered saline; PPARA: peroxisome proliferator activated receptor alpha; PPARG: peroxisome proliferator activated receptor gamma; PPARGC1A: peroxisome proliferator activated receptor, gamma, coactivator 1 alpha; PRDM16: PR domain containing 16; PSAT1: phosphoserine aminotransferase 1; RB1: RB transcriptional corepressor 1; RBL1/p107: RB transcriptional corepressor like 1; SQSTM1: sequestosome 1; sWAT: subcutaneous white adipose tissue; TG: triglycerides; UCP1: uncoupling protein 1 (mitochondrial, proton carrier); WT: wild-type